Cystatin C and Its Role in Patients with Type 1 and Type 2 Diabetes Mellitus. (5th January 2015) - Bashier, Alaaeldin M.; Fadlallah, Ayman Aly Seddik; Alhashemi, Nada; Thadani, Puja Murli; Abdelgadir, Elamin; Rashid, Fauzia
Abstract : Diabetes mellitus is the commonest cause of CKD. It is the leading cause of new patients requiring renal replacement therapy, accounting for 40%, 34%, and 30% of cases in United States, Germany, and Australia, respectively. Recent studies have shown that a low-molecular weight protein, cystatin C, freely filtered by the kidneys is a novel biomarker that may be used for detection of early renal dysfunction in patients with type 1 or type 2 diabetes. Cystatin C has also been shown to detect cardiovascular disease in patients with diabetes and it may also be linked with incident type 2 diabetes in obese patients. We aim to review current evidence based literature on use of cystatin C for early detection of diabetic nephropathy due to type 1 and type 2 diabetes in comparison to conventional methods and explore its association with other comorbidities.